Die gesag van Christus in enkele kerklike gesagsmodelle - Plooy, A. le R. du (Koers, 1988)
Reformed church polity acknowledges a very close relation between Christology and ecclesiology, and intends to be a polity of the kingdom of God. This means the acceptance of Christ as the only Head of His church. He governs the church through the Holy Spirit and the Word of God, and by means of the ministry of the offices. History reveals that although many systems of church government confess the Headship of Christ, analysis of these systems indicates distortions or even elimination of Christ as the one and only Head of the church. A critical review of the systems of the Roman Catholic Church, of Lutheranism, Erastianism, Collegialism and Congregationalism shows that views concerning the authority in the church differ widely. Various forms of authority can be distinguished, i.e. the authority of the pope, office and/or church authority, state government authority in church affairs, etc. In contrast to these viewpoints, the Reformation states that Christ has the only authority in His church. He exercises His government through the offices in the church. These offices are servants and minister His authority in the church. The only authority of the church or the offices is therefore a ministerial authority.